2006
DOI: 10.1002/bse.494
|View full text |Cite
|
Sign up to set email alerts
|

Time horizons of environmental versus non‐environmental costs: evidence from US tort lawsuits

Abstract: One explanation for a positive correlation between environmental and financial performance at the firm level is a bias in firms' investment evaluation processes caused by systematic differences between environmental and other investment opportunities. One of these systematic differences, often hypothesized but still unverified, is that environmental costs occur farther in the future than other costs. We empirically test this hypothesis, and find statistically significant support for it. In our data set the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The barriers receiving the highest average ratings included high upfront expense, high day‐to‐day costs and significant upfront time commitment (Jones, ). Our findings support the findings of other studies that have found costs and time constraints to be among the most significant barriers to implementing environmental management measures (Bendell and Kearins, ; Johnstone and Labonne, ; Jones, ; Marshall et al ., ; Masurel, ; Regnier and Tovey, ; Simpson et al ., ; Stoeckl, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The barriers receiving the highest average ratings included high upfront expense, high day‐to‐day costs and significant upfront time commitment (Jones, ). Our findings support the findings of other studies that have found costs and time constraints to be among the most significant barriers to implementing environmental management measures (Bendell and Kearins, ; Johnstone and Labonne, ; Jones, ; Marshall et al ., ; Masurel, ; Regnier and Tovey, ; Simpson et al ., ; Stoeckl, ).…”
Section: Resultsmentioning
confidence: 99%
“…In one study, Masurel () found cost‐savings to be the most important influence on investment decisions, while important impediments to investments in energy‐saving technologies included the availability of more attractive investment opportunities combined with limitations on capital availability. Regnier and Tovey () suggest that organizations often use discount rates that favor the short term, while the horizon for environmental costs is longer and this leads to apparent underinvestment in environmental performance by firms. In this study, the collective effect of barriers is measured with an index of responses capturing perceived barriers constructed using PCA.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, there is a long period for measuring and quantifying the negative effects in the absence of investments in environmentally friendly policies, technologies, and strategies. An empirical study found that the mean time lag for measuring return on investments in the environmental costs was more than ten years (Regnier & Tovey, 2007). Extended time frames for return on investment decisions tend to motivate business leaders to ignore investments in environmentally friendly technologies because they are under pressure to show improvements in the organizations' performance to their shareholders on a quarterly and annual basis.…”
Section: Tax Savingsmentioning
confidence: 99%
“…Few studies explicitly investigate specific barriers to voluntary environmental management, but among available findings, the most frequently reported issues are time, cost, and a lack of perceived benefits to investing in environmental strategies [3,4,9,17,21,32,43,44,46,106,107]. Findings show that such issues may disproportionately affect SMEs because these organizations: (1) have difficulty keeping abreast of regulatory requirements and supporting compliance costs; (2) experience lower consumer demand for environmental improvements; and (3) may lack an organizational network (e.g., trade association) that supports voluntary environmental management [21,94,104,105,108].…”
Section: Size and Global Market Participationmentioning
confidence: 99%